Implementing Discovery Learning Model to Improve Students' Creative Thinking Skills - Jauziati, Baiq; Nuraini, Nuraini; Sabahanudin, Sabahanudin; Muis, Muhamad Ali; Jalaluddin, Jalaluddin; Mariani, Siti Salmiyatun; Nurulloh, Muh Zulhifzi (Sumber Belajar Sejahtera, 2024)
One alternative learning model is discovery learning, which is a discovery learning model for understanding concepts, meanings, and relationships through an intuitive process that finally concludes; this learning is assumed to be able to improve students' creative thinking skills. This study aims to see the implementation of the discovery learning learning model to enhance students' creative thinking skills. The methods used in this study, observation methods and data recording, were carried out during the learning process through observation using observation sheets and video recording by implementing a technician recording using a mobile phone. The shooting is done thoroughly, and then editing will be done on several events that are considered essential. The results of this study show that lesson study includes plan (planning), do (implementation), and see (reflection) activities. The first lesson study activity is a plan (planning) regarding goal setting, fundamental competency analysis, syllabus, adequate location and time, selecting the correct learning method and model for predetermined material, and preparing a learning implementation plan. The second lesson study activity (the implementation) is done to apply learning strategies to students based on the analysis of student characteristics and experiences and the achievement of learning indicators on light material and its properties. The third activity of the lesson study is see (reflection) on the cognitive, affective, and psychomotor aspects of grade V students of SD Negeri 1 Bagik Payung who have met the achievement of competency indicators.